Factors Affecting Uptake of Agency Banking Services Among Customers in Rural Kenya: A Case of Narok County - Lilian Githae; James Gatauwa; Felix Mwambia (European Scientific Journal, ESJ, 2018)
The objective of this study was to analyze factors affecting uptake of agency banking services among customers in rural Kenya. Specifically, the study sought; to examine the effect of fraud on uptake of agency banking services among customers in Kenya; to determine the extent to which skills of agents affect uptake of agency banking services among customers in Kenya; To establish the effect of location on uptake of agency banking services among customers in Kenya and to find out how confidentiality affect agency banking services uptake among rural customers in Kenya. A multivariate regression model was applied to determine the relative importance of each of the four variables. The findings indicated that bank agent skills, location and confidentiality were found to be statistically significant in explaining uptake of agency banking services. Banks should create awareness to the public that the bank agent’s premises adheres to standard security measures and should also hire security services from security firms to transport cash to and from the agents where necessary. Banks should also train the agency banking agents on how to detect fake money and fraud. The study revealed that agents’ skills affected uptake of agency banking services by rural community in Narok County. The study recommends banks to offer training to agents before they start providing specific services on behalf of the banks to improve their customer handling skills and increase the uptake of the agency banking services.